The Peutz-Jeghers Syndrome. Case Reports - Dorfman, Saúl; Talbot, Ian; Cardozo, José; Tjon, Marucha; Camacho, Shubert (Investigación Clínica, 2013)
Two additional cases of Peutz-Jeghers syndrome are described. One ofthem, a 19 year-old female, Is a sporadic case, whereas in the other case, also a 19 year-old female, there are two members of the family with the Peutz-Jeghers syndrome. A review of some salient features of this entity is made. These include clinical presentation, histopathological factures, malignant potencial and treatment.